Pendidikan Agama Kristen Sebagai Sarana Pembentukan Karakter Dalam Konteks Multikulturalisme - Yuni Tobe; Jindry Tafuli; Semuel Linggi Topayung (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Christian Religious Education (CRE) plays a significant role as a means of character formation for students within the complex multicultural context of Indonesia. CRE not only emphasizes understanding Biblical teachings but also instills values such as love, tolerance, and moral responsibility, which are relevant to cultural and religious diversity. In a diverse society, character education through CRE aims to shape individuals who respect differences, are able to live harmoniously, and serve as